2017
DOI: 10.1002/1878-0261.12138
|View full text |Cite
|
Sign up to set email alerts
|

APE1/Ref‐1 knockdown in pancreatic ductal adenocarcinoma – characterizing gene expression changes and identifying novel pathways using single‐cellRNAsequencing

Abstract: Apurinic/apyrimidinic endonuclease 1/redox factor‐1 (APE1/Ref‐1 or APE1) is a multifunctional protein that regulates numerous transcription factors associated with cancer‐related pathways. Because APE1 is essential for cell viability, generation of APE1‐knockout cell lines and determining a comprehensive list of genes regulated by APE1 has not been possible. To circumvent this challenge, we utilized single‐cell RNA sequencing to identify differentially expressed genes (DEGs) in relation to APE1 protein levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 90 publications
(160 reference statements)
5
45
1
Order By: Relevance
“…These 11 gene sets were then subjected to survival analysis for a better understanding of their role according to a clinical perspective. LIHC, LUAD and PAAD networks, which were composed of bad prognostic genes in high percentages, confirmed previous studies on the important role of APE1 in these cancers [52][53][54][55][57][58][59][60][61][62][63][64][65] . Kaplan-Meier estimation was used to calculate survival probability associated with these genes; the ones having significantly lower survival prognosis (p < 0.05) were used to create cancer-specific PPI subnetworks ( Fig.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These 11 gene sets were then subjected to survival analysis for a better understanding of their role according to a clinical perspective. LIHC, LUAD and PAAD networks, which were composed of bad prognostic genes in high percentages, confirmed previous studies on the important role of APE1 in these cancers [52][53][54][55][57][58][59][60][61][62][63][64][65] . Kaplan-Meier estimation was used to calculate survival probability associated with these genes; the ones having significantly lower survival prognosis (p < 0.05) were used to create cancer-specific PPI subnetworks ( Fig.…”
Section: Discussionsupporting
confidence: 88%
“…In order to focus our attention on the most relevant cancer types, we based our bioinformatic analysis on the eleven datasets having the highest number of bad prognostic genes. Among those, we were interested in particular in liver (LIHC) [52][53][54][55][56] , lung (LUAD) [57][58][59][60] and pancreatic (PAAD) [61][62][63][64][65] cancer datasets, as the essential role of APE1 in the tumorigenic processes of these cancer types is already well established. Notably, the LUAD dataset was the third having the highest number of bad prognostic genes (n = 153).…”
Section: Upstream Regulators Analysismentioning
confidence: 99%
“…APEX1 is a multifunctional protein that interact with multiple transcriptional factors (TFs) to regulate the genes involvement in response to DNA damage, hypoxia and oxidative stress [49]. Our previous study identified significant roles of APEX1 in the regulation of Pa03c cell's response to microenvironmental stresses [50]. Functional enrichment of the differentially expressed genes identified by the methods were further examined.…”
Section: Differential Gene Expression and Gene Co-regulation Analysismentioning
confidence: 99%
“…Comparing to MAST, SCDE, SC2P, EdgeR and DESeq, the downregulated genes in APE1/Ref-1-KD vs. control under hypoxia conditions identified by LTMG-DGE are more significantly enriched to the pathways such as glycolysis, TCA cycle and respiration chain, apoptosis, and lipid metabolism pathways, as well as genes regulated by HIF1A and STAT3 ( Figure 5B and Supplementary Table 7). Note that APE1/Ref-1 directly interacts with HIF1A and STAT3 [50,51], and regulates oxidative stress response, glucose and lipid metabolism, and relevant mitochondrial functions. These results suggest LTMG-DGE method can detect more functionally relevant genes than other tested methods.…”
Section: Differential Gene Expression and Gene Co-regulation Analysismentioning
confidence: 99%
“…APE1 is the key regulator in the cellular oxidative stress pathway, which maintains the activity of numerous cellular transcription factors, such as AP‐1, NF‐κB, Myb, HIF‐1α, HLF, PAX, and p53, through keeping specific cysteine residues in the DNA binding domain reduced state. Moreover, some of these transcription factors are closely related to chemotherapy resistance …”
Section: Introductionmentioning
confidence: 99%